Allergic contact dermatitis from Dittrichia viscosa (L.) Greuter - Gonçalo, S (2012)
9 cases of contact sensitivity to Dittrichia viscosa, mainly with an airborne pattern, are described. All patients reacted to the fresh leaf of the plant and to its ethereal extracts at 1 and 0.5% pet., and some of them also to that at 0.1% pet. Positive reactions to Frullania dilatata, Laurus nobilis, some other members of the Compositae, and helenin were observed, suggesting the diagnosis of a sesquiterpene-lactone-induced allergic contact dermatitis.